Changes in Student Motivation and Teacher Decision Making When Implementing a Formative Assessment Practice - Näsström, Gunilla; Andersson, Catarina; Granberg, Carina; Palm, Torulf; Palmberg, Björn (Frontiers in Education, 2021)
Motivation is a prerequisite for students’ learning, and formative assessment has been suggested as a possible way of supporting students’ motivation. However, there is a lack of empirical evidence corroborating the hypothesis of large effects from formative assessment interventions on students’ autonomous forms of motivation and motivation in terms of behavioral engagement in learning activities. In addition, formative assessment practices that do have an impact on students’ motivation may put additional requirements on teachers than more traditional teaching practices. Such requirements include decisions teachers need to make in classroom practice. The requirements on teachers’ decision-making in formative assessment practices that have a positive impact on students’ autonomous forms of motivation and behavioral engagement have not been investigated. This study describes one teacher's formative assessment practice during a sociology course in upper secondary school, and it identifies the requirements for the teacher’s decision-making. The teacher had participated in a professional development program about formative assessment just prior to this study. This study also investigated the effects of the teacher’s formative assessment practice on the students’ motivation. The teacher’s practice was examined through observations, weekly teacher logs, and an interview with the teacher. Data on changes in the students’ type of motivation and engagement were collected in the teacher’s class and in five control classes through a questionnaire administered in the beginning and the end of the course. The students responded to the questionnaire items by choosing the extent to which they agreed with the statements on a scale from 1-7. The teacher’s formative assessment practice focused on collecting information about the students’ knowledge and skills and then using this information to make decisions about subsequent instruction. Several types of decisions, and the skills required to make them that exceed those required in more traditional teaching practices, were identified. In comparison with the control classes, the teacher’s formative assessment practice had a positive effect on both the students’ controlled and autonomous forms of motivation as well as on their engagement in learning activities.